2017
DOI: 10.22334/jbhost.v2i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Tempeh Juice as Potential Health Support Culinary Tourism

Abstract: Tourism is part of the backbone the supports a country’s economic life.  According to that fact, Indonesia should have a special concern by building a strong branding for it’s tourism.  Tempeh juice culinary is one choice that has big potential to work out, because Indonesian’s most type tourists, they will always have a need to fill the stomach.  The goal of the promotion is to increase the number  of Indonesia’s foreign visitors, by giving impression and belief that tempeh juice as potential health h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Varietas lokal tempe kedelai mengandung sumber gizi penting terutama protein yang terdiri dari 8 jenis asam amino esensial, arginin dan metionin. Tempe juga mengandung vitamin B12 dan antioksidan penting seperti vitamin B2, vitamin E, isoflavon, beta karoten, SOD, dan asam lemak tak jenuh jamak (PUFA) serta mineral (Fe, Cu, Zn, Se, dan Cr) 5 . Kandungan protein dalam tempe 90% lebih tinggi serat dibandingkan tahu.…”
Section: Tempe Kedelaiunclassified
“…Varietas lokal tempe kedelai mengandung sumber gizi penting terutama protein yang terdiri dari 8 jenis asam amino esensial, arginin dan metionin. Tempe juga mengandung vitamin B12 dan antioksidan penting seperti vitamin B2, vitamin E, isoflavon, beta karoten, SOD, dan asam lemak tak jenuh jamak (PUFA) serta mineral (Fe, Cu, Zn, Se, dan Cr) 5 . Kandungan protein dalam tempe 90% lebih tinggi serat dibandingkan tahu.…”
Section: Tempe Kedelaiunclassified
“…Another thing is that most typical culinary Aceh is presented for ceremonial purposes that have not been commercialized. Other research on culinary as tourism attraction, Agung, I. (2017) entitled Tempeh Juice as Potential Health Support Culinary Tourism showed that promotion of tempeh juice should be done consistently and continuously.…”
Section: Introductionmentioning
confidence: 99%